Leadership, Organizational Culture, and Work Motivation on Employee Performance With Job Satisfaction as an Intervening Variable - Sudhana, Andi (Dinasti International Journal of Digital Business Management, 2023)
This study aims to analyze the influence of leadership, organizational culture, and work motivation on the performance of the employees of the Center for Communication Technology Education, Education, Youth, and Sports of the Special Region of Yogyakarta with job satisfaction as an intervening variable. The sample of this study amounted to 40 respondents who were taken using the census method or total sampling. Collecting data using a questionnaire. Instrument test using SPPS ver 20 and data analysis using Smart PLS. Based on the results of the research that has been carried out, it can be concluded that leadership has a positive and significant effect on job satisfaction, Organizational Culture has a positive and insignificant effect on job satisfaction, work motivation has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on employee performance, leadership has a positive and significant effect on job satisfaction. positive and significant impact on employee performance, organizational culture has a positive and insignificant effect on employee performance, work motivation has a positive and insignificant effect on employee performance, leadership has a positive and insignificant effect on employee performance through job satisfaction, organizational culture has a positive and insignificant effect on employee performance through satisfaction work motivation, work motivation has a positive and significant effect on employee performance through job satisfaction.